43. EVALUATION OF THE EFFECTIVENESS OF TEAMWORK COORDINATION IN TEACHING EMERGENCY RESPIRATORY ARREST BY SIMULATING THE CODE BLUE SITUATION ON RESIDENTS (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aims to compare the effectiveness on teamwork skills of two methods: case-based learning and the Code Blue simulation method among resident doctors at the University of Medicine and Pharmacy at Ho Chi Minh city.Methods: This is a prospective observational study conducted on resident doctors from various specialties currently studying at the University of Medicine and Pharmacy at Ho Chi Minh city. One group learn cardiopulmonary resuscitation skills using the Case-Based Learning method, while the other group learn these skills through the Code Blue simulation method. After one year, both groups were reassessed on this skill, and the effectiveness was evaluated using the Teamwork Assessment Scale developed by Kiesewetter J et al. Expectations towards research were assessed by A 5-point Likert scale.Results: There are 177 resident doctors participated in the study, with 87 in the group learning using the Case-Based Learning method and 90 in the group learning using the Code Blue simulation method. The results of the study indicated that the group learning using the Code Blue simulation method showed a statistically significant improvement in the following skills: the team roles were distinct without ambiguity, none of the team members switched their role, the plan for treatment was communicated to all team members, the team leader always reassured that his instructions were understood, and the team members mutually pointed out errors in a very constructive way (with a p-value < 0.001).Conclusions: Teaching cardiopulmonary resuscitation skills using the Code Blue Simulation method shows a significant improvement in skills compared to case-based learning. This effectiveness also highlights the necessity of simulation-based learning for resident doctors.
Keywords: Cardiopulmonary resuscitation, effectiveness, resident doctors.